2018
DOI: 10.1017/s0022149x1800024x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical observation of local inflammatory cell infiltration in the host-tissue reaction site of human hydatid cysts

Abstract: The aim of this study was to evaluate the pattern of local immune cell infiltration in human cystic echinococcosis (CE) by identifying the subtypes of immune cells using immunohistochemistry (IHC). Fifty surgically removed hydatid cyst samples and surrounding tissues were collected from patients referred to Al-Zahra Hospital, Isfahan, Iran. IHC was performed on the surrounding host tissue of hydatid cysts using anti-human CD3, CD19, CD8, CD4, CD68, CD56, Ki-67 and Foxp3 (forkhead box P3) antibodies. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 33 publications
5
18
0
Order By: Relevance
“…Hydatid cysts, the larval stage of E. granulosus s.s. , are able to survive in host tissues for long periods of time, and the liver is the major site of CE involvement. The chronic infection induces an immune imbalance on the hepatic tissue, and gradually forms an immune microenvironment ( Jafari et al., 2019 ; Wen et al., 2019 ). The cellular distribution and functions of immune mediators in the liver are different from those in the periphery; analysis at the site of infection is thus important for deciphering anti- E. granulosus s.s. immunity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydatid cysts, the larval stage of E. granulosus s.s. , are able to survive in host tissues for long periods of time, and the liver is the major site of CE involvement. The chronic infection induces an immune imbalance on the hepatic tissue, and gradually forms an immune microenvironment ( Jafari et al., 2019 ; Wen et al., 2019 ). The cellular distribution and functions of immune mediators in the liver are different from those in the periphery; analysis at the site of infection is thus important for deciphering anti- E. granulosus s.s. immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that T-cell-mediated responses play a key role in the immunology of hydatid cysts in both the mouse experimental model and CE patients ( Rogan, 1998 ; Yasen et al., 2021b ). Accumulated evidence has indicated that T lymphocytes are the predominant inflammatory cells at the site of local host responses to hydatid cysts in humans, cattle and sheep infected with CE ( Sakamoto and Cabrera, 2003 ; Vatankhah et al., 2015 ; Vismarra et al., 2015 ; Jafari et al., 2019 ). In our prior work, we also found that T cells were the most frequent infiltrating cells surrounding the hepatic CE lesions during the establishment phase in experimental mice (after 2 weeks) ( Li et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Elevation of eosinophil count and percentage in patients was observed in our study. Considerable numbers of eosinophils could be recruited into the inflammatory site during the stage of initiation and even proliferation of hydatid [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thiacloprid caused a decrease in the number of eosinophils and neutrophils in the blood. Eosinophils are recognized as end-stage cells involved in protecting the host against parasitic infections [ 43 ]. Once the parasite dies or escapes host immunity, inflammation is mitigated [ 44 ].…”
Section: Discussionmentioning
confidence: 99%